Using Thinking Actively in a Social Context and Spirals in Living Theory research in explanations of educational influences in a global social movement. (May 2019) - Mounter, Joy; Huxtable, Marie; Whitehead, Jack
The article's authors continually ask and attempt to answer questions, such as, 'How do I improve what I am doing?' and 'How do we improve what we are doing?' by researching their practice and making public what knowledge they create along the way. Here they describe Living Theory research and explain why this has enabled them to improve their practice and hold themselves to account to others and themselves to give expression in practice to their values that contribute to the flourishing of humanity. Drawing on Thinking Actively in a Social Context (TASC), the integration of research and practice is exemplified. They finally illustrate how educational professionals in diverse fields and contexts of practice have contributed to the growth of a global educational knowledge base comprising the valid values-based explanations of educational-practitioners of their educational influences in their own learning, the learning of others and the learning of the social formations they live and work in.